A comparison of transversus abdominis plane block with quadratus lumborum block for post-operative analgesia in abdominal hysterectomy: a retrospective observational study - Gupta, Sumit Kumar; Grewal, Ritu; Anne, Sirisha; Garg, Arpit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Abdominal hysterectomy is the most common surgery performed in Indian Women. Recent advances in Regional Anaesthesia especially ultrasonography-guided truncal blocks for postoperative analgesia are now being used for patient comfort and faster times for discharge of the patients. This study compares the ultrasonographic guided transversus abdominis plane block and quadratus lumborum blocks for patients undergoing abdominal hysterectomy under general anaesthesia. Aim of the study was to compare the efficacy of transversus abdominis plane block and quadratus lumborum blocks in patients undergoing abdominal hysterectomy. Methods: A retrospective observational study of prospectively collected data was performed. A total of 111 patients of American Society of Anesthesiologists (ASA) II and III gradings were enrolled in the study who had received either transversus abdominis plane block or quadratus lumborum blocks. Visual analog scale (VAS) scores and use of rescue analgesia was studied between the two groups. The data obtained were analysed using the students t-test and Mann Whitney U Test. Results: The demographic profile was similar between the 2 groups. The study showed that patients who received the quadratus lumborum block had a greater analgesia after 6 hours and had lower analgesic requirements compared to those who received transversus abdominis block (TAP) block. TAP block was however effective in the initial post-operative period. Conclusions: In patients undergoing abdominal hysterectomy quadratus lumborum block may be preferred over TAP block for post-operative analgesia.